Prospects and Difficulties of Bilateral Relations between Bangladesh and the United States: An Analysis - Akter, Sinzina (The Jahangirnagar Review Part-C, 2025)
Bangladesh gained US recognition on April 4, 1972, following its independence on December 16, 1971. May 18, 1972, saw the establishment of diplomatic ties with the American Embassy in Dhaka. The US has grown to be one of Bangladesh’s main trading partners and has given development support in sectors including economic growth, health, and education. Bangladesh and the United States collaborate to fight terrorism in order to advance regional stability. Due to political and human rights issues, the US-Bangladesh bilateral partnership has certain difficulties. The US has criticized the Bangladeshi government for restricting free expression and holding corrupt elections. The Rapid Action Battalion has been subject to penalties by the US government for human rights violations. Bangladesh is currently going through a political transition, which may present a chance for the US to collaborate with Bangladesh. They are able to identify the difficulties and change the connection going forward. Bangladesh’s July Movement against the former prime minister created a fresh chance for this partnership. The former Bangladeshi government has come under fire from the US for violating human rights and persecuting opposition members. The United States has stated that it wants an elected government to take office as soon as possible and has offered support to the interim administration since Bangladesh’s political landscape has shifted. There were other difficulties in the two nations’ economic relationship as well. One of Bangladesh’s main sources of foreign direct investment is the United States. The United States contributes to the education section through scholarships and fellowship programs. There are security issues with the USBangladesh connection as well. Both nations are conscious of South Asia’s security and climate change. The United Nations, ASEAN Regional Forum, International Monetary Fund, World Bank, and World Trade Organization are just a few of the international organizations that both Bangladesh and the United States are members of. The prospects and difficulties in Bangladesh-US relations are examined in this paper, with an emphasis on which sectors are better suited to their economies and democracies. The study is based on an extensive analysis of academic publications, records, and internet research papers about bilateral relations between the United States and Bangladesh. Additionally, the study investigates the fields that influence US relations with Bangladesh. The objective of this analysis is to assess the prospects for USBangladesh relations. This paper offers a thorough analysis of the USBangladesh relationship in an effort to determine whether the two countries might cooperate to strengthen their economies, democracies, and responses to global climate change while also alleviating their own stresses.